The Winnipeg and Hudson Bay Railway, forming with Hudson Bay and Strait, a new trade route between America and Europe [electronic resource] : the most important railway enterprise of the age : a saving of 1,000 to 1,500 miles of railway carriage. - Winnipeg and Hudson Bay Railway. ([Winnipeg? : s.n.], 1887)
Electronic reproduction. Mode of access: Internet. 44